A20 suppresses hepatocellular carcinoma proliferation and metastasis through inhibition of Twist1 expression. Issue 1 (December 2015) - Chen, Haiyang; Hu, Liang; Luo, Zaili; Zhang, Jian; Zhang, Cunzhen; Qiu, Bijun; Dong, Liwei; Tan, Yexiong; Ding, Jin; Tang, Shanhua; Shen, Feng; Li, Zhong; et al.
Abstract Background Aberrant expression of A20 has been reported in several human malignancies including hepatocellular carcinoma (HCC). However, its clinical relevance and potential role in HCC remain unknown. Methods Quantitative PCR, Western blots and immunohistochemistry analyses were used to quantify A20 expression in HCC samples and cell lines. The correlation of A20 expression with clinicopathologic features was analyzed in a cohort containing 143 patients with primary HCC. Kaplan-Meier curves were used to evaluate the association between A20 expression and patient survival. Functional studies were performed to determine the effects of A20 on proliferation and metastasis of HCC cells in vitro and in vivo. Results Expression of A20 was increased in HCC tissues and cell lines. Increased expression of A20 was negatively correlated with the tumor size, TNM stage, tumor thrombus formation, capsular invasion and serum AFP levels. Patients with higher A20 expression had a prolonged disease-free survival and overall survival than those with lower A20 expression. Forced expression of A20 significantly inhibited the proliferative and invasive properties of HCC cells both in vitro and in vivo, whereas knockdown of A20 expression showed the opposite effects. Further studies revealed that expression of A20 was inversely correlated with Twist1 levels and NF-κB activity in HCC tissues and cell lines. A20-induced suppression of proliferation and migration of HCC cells were mainly mediated through inhibition of Twist1 expression that was regulated at least partly by A20-induced attenuation of NF-κB activity. Conclusions Our results demonstrate that A20 plays a negative role in the development and progression of HCC probably through inhibiting Twist1 expression. A20 may serve as a novel prognostic biomarker and potential therapeutic target for HCC patients.